Academics' views towards the internal quality assurance system of St. Mary's University in Ethiopia. (3rd April 2022) - Tamrat, Wondwosen
ABSTRACT: This study explored, through a quantitative case study approach, the views of academics toward the importance and components of an internal quality assurance system of St Mary's University in Ethiopia. The findings revealed that while academics value positively the importance of an internal quality assurance system in general and institutional frameworks deployed to achieve the same goal in particular, they are critical of the limited level of engagement at the lower levels of the system. This suggests the need for strengthening grassroot functional units and effectively integrating the participation of academics and students in future internal quality assurance efforts.